2021
DOI: 10.3389/fncel.2021.619777
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Function and Dysfunction in Lysosomal Storage Diseases

Abstract: Lysosomal storage diseases (LSDs) with neurological involvement are inherited genetic diseases of the metabolism characterized by lysosomal dysfunction and the accumulation of undegraded substrates altering glial and neuronal function. Often, patients with neurological manifestations present with damage to the gray and white matter and irreversible neuronal decline. The use of animal models of LSDs has greatly facilitated studying and identifying potential mechanisms of neuronal dysfunction, including alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 116 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…The relationship between the aberrant accumulation of proteins and lipids in the LE/Lys and synaptic dysfunction, although commonly observed in lysosomal storage disorders, is still incompletely understood at the mechanistic level. 53 CLN3 has been proposed to be present in synaptosomes 54 and recent studies in JNCL model systems support that neuronal network dysfunction and synaptic alterations may in fact precede aberrant LE/Lys storage. 55 , 56 We observed that proteins downregulated in JNCL LE/Lys compared to controls were associated with the glutamatergic and GABAergic synapse KEGG pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the aberrant accumulation of proteins and lipids in the LE/Lys and synaptic dysfunction, although commonly observed in lysosomal storage disorders, is still incompletely understood at the mechanistic level. 53 CLN3 has been proposed to be present in synaptosomes 54 and recent studies in JNCL model systems support that neuronal network dysfunction and synaptic alterations may in fact precede aberrant LE/Lys storage. 55 , 56 We observed that proteins downregulated in JNCL LE/Lys compared to controls were associated with the glutamatergic and GABAergic synapse KEGG pathways.…”
Section: Discussionmentioning
confidence: 99%
“…We found that large synaptophysin aggregates co-localized with Lamp1 staining ( Fig. 5C , white arrows), suggesting a lysosomal-mediated synaptophysin accumulation and lysosomal-mediated mechanism of synaptic failure 56 .…”
Section: Resultsmentioning
confidence: 82%
“…We found that large synaptophysin aggregates co-localized with LAMP1 staining ( Figure 5 C, white arrows) in untreated Naglu −/− mice, suggesting a lysosomal-mediated synaptophysin accumulation and mechanism of synaptic failure. 34 Alternatively these aggregates may end up in the lysosome and may fail to be broken down.
Figure 5 Correction of synaptophysin aggregation in Naglu −/− mice at 9 months (A) Representative bright-field images of 40-μm-thick half-brain coronal sections from Naglu +/− mice (Unaffected) and Naglu −/− mice injected with saline (Vehicle −/−) or N-IGFII- iNSCs (T (N-IGFII) −/−) immunohistochemically stained for synaptophysin.
…”
Section: Resultsmentioning
confidence: 99%